Jean D'Espagnet's the summary of physics restored : the 1651 translation with D'Espagnet's Arcanum (1650) /: the 1651 translation with D'Espagnet's Arcanum (1650). (2019) - Espagnet, Jean d', 1564-approximately 1637
No abstract available